Izgubljene in najdene knjige iz nekdanje Kopitarjeve knjižnice - Dular, Anja (Slavistična revija, 2011)
The article discusses the issues of Kopitar's library or rather, the fate of his books that are presently not curated by the National and University Library in Ljubljana. It is assumed that some of the books were first held in Vienna by one of the auctioneers, Matthäus Kuppitsch, and later they found their way to the Britisch Library through the mediation of a Berlin bookseller, Adolf Asher.
Keywords: Britanska knjižnica; knjižnice; Kopitar, Jernej, 1780-1844; slovenski jezikoslovci; zasebne knjižnice